February house - Tippins, Sherill (Houghton Mifflin, 2005)
The story of an extraordinary experiment in communal living, one involving young but already iconic writers--and the country's best-known burlesque performer--in a house in Brooklyn during 1940 and 1941. It was a fevered yearlong party fueled by the appetites of youth and by the shared sense of urgency to take action as artists in the months before America entered the war. In spite of the sheer intensity, the house was for its residents a creative crucible. Carson McCullers's two masterpieces, The Member of the Wedding and The Ballad of the Sad Cafe, were born here. Gypsy Rose Lee, workmanlike by day, party girl by night, wrote her book The G-String Murders in her bedroom. W. H. Auden, who along with Benjamin Britten was being excoriated at home in England for absenting himself from the war, presided over the house like a peevish auntie, collecting rent money and dispensing romantic advice. And yet all the while he was composing some of the most important work of his career.